Mesenchymal chondrosarcoma of the jaws: A series of two rare cases - Satya Ranjan Misra; G Maragathavalli; Vineet Daniel Alex; Sobhan Mishra (Wolters Kluwer Medknow Publications, 2012)
Chondrosarcoma (CS) is a malignant neoplasm that results in abnormal bone and cartilage growth. Although CS is rare, it is the second most common primary bone malignancy. Mesenchymal chondrosarcoma (MC) is a rare histological variant of CS that accounts for only about 1 % of all CS and has high predilection for the head and neck region. It is usually seen in younger age group compared to conventional CS and the maxillary alveolus is the most common site. The tumor is unique because of its aggressive growth with a high tendency for late recurrence and delayed metastasis- We present two cases of MC, one case involving the mandibular condyle and the second, a metastatic CS with the primary in the clavicle.